2023
DOI: 10.1038/s41467-023-43188-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological forecasts for marine resource management during climate extremes

Stephanie Brodie,
Mercedes Pozo Buil,
Heather Welch
et al.

Abstract: Forecasting weather has become commonplace, but as society faces novel and uncertain environmental conditions there is a critical need to forecast ecology. Forewarning of ecosystem conditions during climate extremes can support proactive decision-making, yet applications of ecological forecasts are still limited. We showcase the capacity for existing marine management tools to transition to a forecasting configuration and provide skilful ecological forecasts up to 12 months in advance. The management tools use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The forecasts displayed in Figure 4 inspire plans to expand operational forecasting systems (e.g., psl.noaa.gov/marine-heatwaves/#forecasts, and https://www.mercatorocean.eu/en/category/mhw-bulletin/) to represent marine biogeochemistry, allowing for outlooks on extremes in key ecosystem stressors. Accurate forecasts of marine dynamics and extremes can better inform contemporary practices of marine managers, especially in a changing climate [8,41,42]. While our study does not make concrete policy recommendations, we hope that this work encourages the inclusion of biogeochemical and carbon cycle models in operational forecasts and seasonal outlooks that currently only include physical tracers.…”
Section: Outlook For Extreme Events In 2024mentioning
confidence: 91%
“…The forecasts displayed in Figure 4 inspire plans to expand operational forecasting systems (e.g., psl.noaa.gov/marine-heatwaves/#forecasts, and https://www.mercatorocean.eu/en/category/mhw-bulletin/) to represent marine biogeochemistry, allowing for outlooks on extremes in key ecosystem stressors. Accurate forecasts of marine dynamics and extremes can better inform contemporary practices of marine managers, especially in a changing climate [8,41,42]. While our study does not make concrete policy recommendations, we hope that this work encourages the inclusion of biogeochemical and carbon cycle models in operational forecasts and seasonal outlooks that currently only include physical tracers.…”
Section: Outlook For Extreme Events In 2024mentioning
confidence: 91%
“…A larger ensemble size may also increase skill more if it was a multimodel ensemble, consisting of downscaled predictions forced by different models and/or using different models for downscaling, rather than just an ensemble of multiple runs from the same model. For example, Brodie et al (2023) found significantly higher skill in an ensemble of 73 members from 6 different coarse resolution models compared to a much smaller ensemble of 3 coarse or downscaled models.…”
Section: Skill Versus Ensemble Sizementioning
confidence: 96%
“…Although dynamical downscaling offers the possibility of running multiple ensemble members to provide information about forecast uncertainty, the substantial computational cost of high resolution models used for downscaling has constrained the ensemble sizes of past climate downscaling efforts (Drenkard et al, 2021). In an analysis of seasonal forecasts for the California Current System, Brodie et al (2023) found that although a small ensemble of downscaled forecasts outperformed a subset of the same size from a much larger ensemble of coarse resolution forecasts, the full ensemble of coarse resolution forecasts outperformed the small downscaled ensemble. Furthermore, in some cases high ocean resolution has been found to actually degrade forecast skill (Sandery and Sakov, 2017;Thoppil et al, 2021).…”
mentioning
confidence: 99%
“…Furthermore, skilful forecasts of MHWs, with lead up times of 12 months, have recently become operational (Jacox et al, 2022) and can be integrated into our model framework to forecast future changes in fishing grounds. Such approaches can offer early warning to managers and fishing fleets at relevant time scales for decision-making (Brodie et al, 2023). Although existing adaptive strategies (e.g.…”
Section: Con Clus Ions: Implic Ations For Climate-re S Ilient Fis Her...mentioning
confidence: 99%